POLITICAL AND LEGAL BASES OF THE POLITICAL OPPOSITION IN UKRAINE - Цимбал, Д.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article highlights the background and specifics of the institute of political opposition in Ukraine, as well as the necessity to address the issue of the legal status of the consolidation of the opposition. The article analyzes the lawmaking Ukrainian deputies in the aspect of institutionalization of the opposition, served examples legal consolidation status of the parliamentary majority and the minority in various democratic countries , and expressed the view that the development and adoption at the legislative level legal act that would regulate the rights and obligations of the political opposition.